DECONSTRUCTING THE THREAT OF TECHNOLOGY: A CRITIQUE OF SURVEILLANCE CAPITALISM AND ITS IMPLICATIONS FOR E-DEMOCRACY - Utama, Rafif Sakti; Rahmatunnisa, Mudiyati; Solihah, Ratnia (JWP (Jurnal Wacana Politik), 2025)
This study critiques the phenomenon of surveillance capitalism in the digital era, focusing on its impact on digital democracy or e-democracy in Indonesia. Drawing from Shoshana Zuboff’s framework, surveillance capitalism leverages human behavioural data as raw material for commercial predictions, threatening privacy, fostering polarization, and weakening the digital public sphere. Using a qualitative literature-based approach and semi-structured interviews with experts and practitioners, the research validates its findings through data triangulation across journal articles, policy reports, and interview insights. The results indicate that social media algorithms contribute to the spread of disinformation, political polarization, and the manipulation of public opinion. For instance, during the 2024 elections in Indonesia, algorithms were found to amplify echo chambers, reduce exposure to diverse perspectives, and promote sensational content. The study concludes that technology’s negative impacts are shaped by the economic structures and designs underlying its use, underscoring the need for regulatory frameworks and public awareness to address these challenges.